2013
DOI: 10.1590/s0080-62342013000200026
|View full text |Cite
|
Sign up to set email alerts
|

Manejo da dor de pacientes com aids: análise da estrutura gerencial em hospital de referência

Abstract: O objetivo deste estudo foi analisar a estrutura gerencial para o manejo da dor em pacientes com aids em um hospital de referência de Fortaleza, CE, Brasil. Pesquisa descritiva com enfoque qualitativo, desenvolvida no ano de 2010. Foram realizadas 20 entrevistas com profissionais de saúde (médicos e enfermeiros), analisadas segundo o referencial da análise de conteúdo. Os dados foram organizados em categorias: condições estruturais favoráveis e desfavoráveis. Constatou-se prevalência de condições desfavoráveis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…According to the International Association for the Study of Pain (IASP), pain is "an unpleasant sensory and emotional experience associated with an existing or potential injury, or described in terms of such injury." When named as "chronic pain," it is characterized as continuous or recurrent pain, lasting at least for three months, often with uncertain etiology, and does not disappear with the use of conventional therapeutic procedures, becoming the cause of prolonged incapacity and disability 28,29 . This study confirms the data presented in the literature since almost 70% of the sample reported pain with chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Association for the Study of Pain (IASP), pain is "an unpleasant sensory and emotional experience associated with an existing or potential injury, or described in terms of such injury." When named as "chronic pain," it is characterized as continuous or recurrent pain, lasting at least for three months, often with uncertain etiology, and does not disappear with the use of conventional therapeutic procedures, becoming the cause of prolonged incapacity and disability 28,29 . This study confirms the data presented in the literature since almost 70% of the sample reported pain with chronicity.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, deve-se reestruturar o modelo de gerenciamento do cuidado ao paciente hospitalizado, aprimorar os recursos organizacionais, materiais e humanos atuantes, capacitando--os para a avaliação da dor como rotina e para a cultura de análises e registros acurados desse sintoma, para que terapêu-ticas sejam melhor implementadas e garantam satisfação analgésica ao paciente (7) .…”
Section: (E11)unclassified
“…Se os opióides forem administrados corretamente por profissionais de saúde capacitados, não existe o problema do vício. Para tanto, faz-se necessário que tais medicamentos estejam amplamente acessíveis aos pacientes com dores muito fortes e constantes e que os profissionais sejam habilitados para saber como e quando usá-los (7) . Cabe salientar que o fato do tratamento medicamentoso ser um aspecto importante no cuidado a esses pacientes, por trazer o conforto imediato no âmbito fisiológico, não se deve deixar de visualizar as questões subjetivas que envolvem a experiência dolorosa.…”
Section: Eu Pouco Uso Dolantina Porque Tem Uma Dependência Muito Graunclassified
“…The scales available for patients' behavioral assessment are the Children's and Infant's Postoperative Pain Scale (CHIPPS) and the Neonatal Infant Pain Scale (NIPS) (6,9) . School-age children tend to express subjectivity more assertively by qualifying and quantifying their pain and providing more accurate information.…”
Section: Introductionmentioning
confidence: 99%